Peace Counseling in the Scientific Spotlight: A Bibliometric Analysis of Global Research Trends - Saputra, Wahyu Nanda Eka (Buletin Konseling Inovatif, 2025)
This study aims to map global trends in peace counseling research using a bibliometric approach. Data were taken only from the Scopus database, focusing on publications containing keywords related to peace counseling, such as peace counseling, peace psychotherapy, and peacebuilding therapy. The analysis was conducted on 769 selected documents published between 1937 and 2025. The results showed a significant increase in publications since 2020, reflecting the growing need for counseling approaches that support peace and psychological well-being. Authors from various countries made different contributions, with the United States dominating the number of publications and citations, while developing countries such as Indonesia began to show significant participation. However, the findings also showed that collaboration between researchers and institutions is still limited, indicating the need to strengthen global scientific networks. Popular topics that emerged in this study included psychotherapy, psychological well-being, peace education, and the role of counselors in building peace. The results of this study provide an important contribution to understanding the development and direction of peace counseling research at the international level, as well as providing a basis for developing counseling policies and practices that are more relevant to contemporary social needs. This study also encourages further research incorporating qualitative approaches to explore the local context and practical implementation of peace counseling in more depth.